Boundary shear stress distribution for a converging compound channel. Issue 2 (3rd May 2016) - Naik, B.; Khatua, Kishanjit K.
Abstract: The boundary shear force distribution in open channel flow is needed for various purposes such as the flow resistance relationship, for designing stable channels. During floods, river overtops the main channel and flows over the flood plain located to its sides. For such compound channels the flow structure becomes complicated due to the transfer of momentum between the deep main channel and the adjoining flood plains that magnificently affects the shear stress distribution in flood plain and main channel subsections. Due to the rapidly growing population and the consequent demand for food and accommodation, more and more land on floodplain regions of a river system has been used for agriculture and settlement. This also causes flood plain geometry to vary along the length of the flow called converging compound channel. In this paper an experimental investigation concerning the distribution of shear stress in the main channel and flood plain of the converging compound channels are presented. Based on the experimental results of boundary shear, a new equation is developed for predicting boundary shear stress distribution in terms of non-dimensional geometric and flow variables.